Community Outreach and Tuberculosis Prevention through Chest Imaging Screening in Batursari Village, Mranggen, Demak - Gatot Murti Wibowo; Brian Ilham Pranandya (Poltekkes Kemenkes Semarang, 2026)
Tuberculosis (TBC) remains a significant public health issue in Indonesia, with the country ranking high for TBC cases globally, as reported by the World Health Organization (WHO). The lack of awareness and limited access to early detection methods contribute to the high rate of late-stage TBC diagnoses. To address this, community outreach activities involving health education and chest imaging screenings were conducted in Batursari Village, Kecamatan Mranggen, Demak. The primary objective was to enhance community awareness regarding TBC and provide accessible chest imaging screening. A total of 42 participants, including suspected TBC patients and their families, participated in the program. The results revealed that while most participants had normal chest imaging findings, some required further examinations due to suspicious abnormalities. This paper discusses the methods used, outcomes, and the importance of such preventive measures in combating the spread of TBC.